The Views of Imam Al-Tabari on the Night of Isra and Mi'raj - Sweia, Naima Abu Al-Qasim (Journal of Humanities & Social Sciences, 2018)
The article addresses the views of Imam Al-Tabari on the night of Isra and Mi'raj. The importance of this article lies in the precise presentation of the details of the journey of Isra and Mi'raj from the Sacred Mosque to Al-Aqsa Mosque, and how the Messenger of Allah traveled with Jibril (peace be upon him) using Al-Burāq([1]), to pray at Al-Aqsa mosque and then going to the heavens and the details of his trip there. The objectives of this article are to clarify and to highlight the views of Imam Al-Tabari on the merits of the journey of Isra and Mi'raj. It also focuses on revealing the views of the people of interpretation regarding the events of this trip.From this article, we reach several conclusions, the most important of which is the truth of the Miracle of Isra and Mi'raj, the miracle of the great journey scenes, the scenes of the ascending to Heaven, the miracle of going out of Mecca to Jerusalem in the same night, and the miracle of Al-Burāq, it was the animal that God created. Everything about Al-Burāq was a miracle. Its color was a miracle, it would put its foot in a place and it would block the whole horizon of the eyesight, and the camels were afraid of the sound of its feet that they fled to the desert. Knowing all of that, Al-Burāq was not the only wonderful thing, but all that the Prophet saw is considered to be miracles that give advice, guidance, and vision to all people. ([1]) Al-Burāq is the creature from the heavens that carried the Islamic prophet Muhammad from Mecca to Jerusalem and back during the Isra and Mi'raj or "Night Journey", as recounted in hadith literature.
Keywords: the incident of Isra and Mi'raj; the Prophet Muhammad; Imam al-Tabari